2009
DOI: 10.1074/jbc.m109.025791
|View full text |Cite
|
Sign up to set email alerts
|

Cold Shock Domain Protein 3 Regulates Freezing Tolerance in Arabidopsis thaliana

Abstract: In response to cold, Escherichia coli produces cold shock proteins (CSPs) that have essential roles in cold adaptation as RNA chaperones. Here, we demonstrate that Arabidopsis cold shock domain protein 3 (AtCSP3), which shares a cold shock domain with bacterial CSPs, is involved in the acquisition of freezing tolerance in plants. AtCSP3 complemented a cold-sensitive phenotype of the E. coli CSP quadruple mutant and displayed nucleic acid duplex melting activity, suggesting that AtCSP3 also functions as an RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 45 publications
(64 reference statements)
9
114
2
Order By: Relevance
“…Comparative sequence analysis revealed multiple discrepancies in cis-element regions which may impart transcriptional control over this gene locus (79). Using transgenic overexpression lines for the well characterized abiotic stress related CBF/DREB transcription factors, we confirmed that AtCSP3 (At2g17870), which is a regulator of cold acclimation (33), is targeted by the CBF3/DREB1A transcription factor (unpublished results).…”
Section: Regulation Of Cold Shock Domain Gene Expressionsupporting
confidence: 52%
See 3 more Smart Citations
“…Comparative sequence analysis revealed multiple discrepancies in cis-element regions which may impart transcriptional control over this gene locus (79). Using transgenic overexpression lines for the well characterized abiotic stress related CBF/DREB transcription factors, we confirmed that AtCSP3 (At2g17870), which is a regulator of cold acclimation (33), is targeted by the CBF3/DREB1A transcription factor (unpublished results).…”
Section: Regulation Of Cold Shock Domain Gene Expressionsupporting
confidence: 52%
“…In the case of plant CSPs, no evidence has been produced to suggest that they may function to directly affect transcription. However, CSPs from wheat and Arabidopsis are localized to the nucleus (30,(32)(33)(34)53), which indirectly supports a putative functional role related to transcription.…”
Section: Transcriptionmentioning
confidence: 80%
See 2 more Smart Citations
“…Compared with wild type, a knockout mutant of AtCSP3 is more sensitive to freezing, drought, and salt stresses. 26,27 Conversely, overexpression of AtCSP3 confers enhanced stress tolerance. 26,27 AtCSP3 regulates the expression of abiotic stress responsive genes, but the functions of these genes are mostly unknown.…”
mentioning
confidence: 99%